Tropospheric temperature response to stratospheric ozone recovery in the 21st century - Hu, Y.; Xia, Y.; Fu, Q. (Atmospheric Chemistry and Physics, 2011)
Recent simulations predicted that the stratospheric ozone layer will likely return to pre-1980 levels in the middle of the 21st century, as a result of the decline of ozone depleting substances under the Montreal Protocol. Since the ozone layer is an important component in determining stratospheric and tropospheric-surface energy balance, the recovery of stratospheric ozone may have significant impact on tropospheric-surface climate. Here, using multi-model results from both the Intergovernmental Panel on Climate Change Fourth Assessment Report (IPCC-AR4) models and coupled chemistry-climate models, we show that as ozone recovery is considered, the troposphere is warmed more than that without considering ozone recovery, suggesting an enhancement of tropospheric warming due to ozone recovery. It is found that the enhanced tropospheric warming is mostly significant in the upper troposphere, with a global and annual mean magnitude of similar to 0.41K for 2001-2050. We also find that relatively large enhanced warming occurs in the extratropics and polar regions in summer and autumn in both hemispheres, while the enhanced warming is stronger in the Northern Hemisphere than in the Southern Hemisphere. Enhanced warming is also found at the surface. The global and annual mean enhancement of surface warming is about 0.16K for 2001-2050, with maximum enhancement in the winter Arctic. Meteorology & Atmospheric Sciences SCI(E) 11 ARTICLE 15 7687-7699 11